PENERAPAN PEMBELAJARAN TEMATIK DI MI AL HASIB PAKIS MALANG PADA MASA PANDEMI COVID-19 - Nanik Nur Hidayah; Rosichin Mansur; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
The world of education today, learning in elementary schools or madrasah ibtidaiyah has implemented the 2013 curriculum. The curriculum in its teaching and learning approach uses thematic learning. This learning is a hope for students to develop their abilities and gain hands-on experience. Based on observations, researchers found that the covid-19 pandemic had an impact on Madrasah Ibtidaiyah Al Hasib Pakis Malang. Problems that arise include changes in education in the teaching and learning process to be hampered and less conducive, especially in thematic learning. During the covid-19 pandemic, a collaborative education system was implemented between offline and online. Offline is done by home visit, while online is done by whatsapp group media. Limited time for learning which is carried out for 2 hours and limited facilities and infrastructure. Kata kunci: Implementation, Thematic Learning, Covid-19 Pandemic